Application of Pancasila student profile character education in thematic learning - Erna Budiarti; Rasintha Suci Ramadhan; Laely Farokhah (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2023)
The aims of this study are: (1) Describe the planning of the thematic learning of Pancasila student profiles? (2) Describe the implementation of the thematic learning of Pancasila student profiles; (3) Describe the evaluation of the thematic learning of Pancasila student profiles in grade 2 MI Madinatunnajah. This research method uses descriptive qualitative with case studies in class 2 MI Madinatunnajah. Data obtained through observation, interviews, and documentation. The steps of the data analysis technique are data reduction, data presentation, and conclusions. The validity of the data was checked through credibility, transferability, dependability, and confirmability tests. The results of the study conclude that: MI Madinatunnajah has implemented integrated learning for Pancasila student profiles, it's just that this has not been officially enforced, because there has been no socialization from the government about integrated learning for Pancasila student profiles. Learning planning at MI Madinatunnajah contains indicators of the profile of Pancasila students, one of which is about God Almighty, on this indicator MI Madintunnajah applies it to everyday life, especially in the school environment. The implementation of learning at MI Madinatunnajah also has indicators for the profile of Pancasila students. Various indicators of the profile of Pancasila students, the homeroom teacher of MI Madinatunnajah 2 applied the thematic learning during the lesson and adjusted between the 6 indicators of the Pancasila student profile and the theme material in the thematic package book. In the evaluation of the 2nd grade homeroom teacher, MI Madinatunnajah has also implemented the Pancasila student profile indicator. The assessment carried out by the homeroom teacher of MI Madinatunnajah is in the form of assessment of assignments, exams and given projects. Each of the assessments aims to determine students' understanding of the material they are learning and understanding of the indicators of the Pancasila student profile and Pancasila values.